2021
DOI: 10.1051/e3sconf/202132506014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Gender Role in Unemployment: How Women in Special Capital Region of Jakarta is Less Likely to be Unemployed During Economic Disturbance

Abstract: The gender gap that occurs in Special Capital Region of Jakarta, between men and women has an impact on aspects of employment related to labor absorption. Increasing the number of optimal employment opportunities, both in terms of productivity and efficiency, can determine the success of economic development in a region. This study was conducted to see how likely it is that women are unemployed, in relation to the employment aspect in Special Capital Region of Jakarta which is based on secondary data from BPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Based on previous studies, the sleeplessness experience is caused by some factors, including concerns related to work, school, health, finances, and family [42][43][44]. Accordingly, the tendency of males to have more sleeplessness experience than females in Indonesia is cogent based on the fact that the average male labor participation rate was about 81.5 percent and 56.7 percent of them work in the informal sector [45]. Interestingly, the cross-sectional study conducted in the UK involving 8547 respondents reported that females were more sleepless than males due to being more influenced by their emotional reaction to the pandemic.…”
Section: Mental Stress and Sleeplessness Associated With Socio-demogr...mentioning
confidence: 99%
“…Based on previous studies, the sleeplessness experience is caused by some factors, including concerns related to work, school, health, finances, and family [42][43][44]. Accordingly, the tendency of males to have more sleeplessness experience than females in Indonesia is cogent based on the fact that the average male labor participation rate was about 81.5 percent and 56.7 percent of them work in the informal sector [45]. Interestingly, the cross-sectional study conducted in the UK involving 8547 respondents reported that females were more sleepless than males due to being more influenced by their emotional reaction to the pandemic.…”
Section: Mental Stress and Sleeplessness Associated With Socio-demogr...mentioning
confidence: 99%